TELEMEDICINE DISRUPTION: A COMPREHENSIVE NARRATIVE LITERATURE REVIEW ON PHYSICIANS’ PERSPECTIVES. - Kumar, Pramod (Student’s Journal of Health Research Africa, 2024)
Telemedicine, the delivery of healthcare services via telecommunications technology, has evolved significantly since the early 20th century. This evolution has been propelled by advancements in digital technology and heightened by the demands of modern healthcare challenges, including the COVID-19 pandemic. Telemedicine offers enhanced access to care, improved patient engagement, and potential cost savings, but it also introduces unique challenges and disruptions to traditional medical practice. This literature review aims to systematically examine and synthesize existing research on physicians’ perspectives regarding the disruptions caused by telemedicine, identifying common themes, challenges, and opportunities that influence its integration into routine clinical practice. The review traces the evolution of telemedicine, highlighting key milestones from early radiologic image transmission to the integration of AI-driven tools. Theoretical frameworks like Innovation Diffusion Theory, Technology Acceptance Model, and Disruptive Innovation Theory are explored to understand telemedicine adoption among healthcare providers. The adoption by physicians is influenced by factors such as technological literacy and organizational support, with barriers like data security concerns. Various telemedicine models, including store-and-forward, real-time video consultations, and remote monitoring, are discussed in the context of services ranging from primary care to chronic disease management. Physicians’ experiences with telemedicine reveal challenges in quality of care and technical issues, emphasizing the need for comprehensive training and education. The review highlights the necessity for ongoing Continuing Medical Education, certification, and licensure standardization in telemedicine. It suggests a future where telemedicine is seamlessly integrated into healthcare systems, with physicians adept in its use through tailored, hands-on training experiences. To optimize the use of telemedicine in clinical practice, policies must focus on standardizing training and licensure, ensuring data security, and addressing reimbursement issues. Emphasis should be placed on developing clinical guidelines that adapt to the evolving landscape of telemedicine.